(untitled) - Johnson, Mark W. (Boston, 2018)
Business model innovation is the key to unlocking transformational growth--but few executives know how to apply it to their businesses. In Reinvent Your Business Model, Mark Johnson reveals the playbook. Johnson lays out an eminently practical framework that identifies the four fundamental building blocks that make business models work. In a series of in-depth case studies, he goes on to vividly illustrate how companies are using innovative business models to achieve transformational growth by - fulfilling unmet customer needs in their current markets - serving entirely new customers and creating new markets - and responding to tectonic shifts in market demand, government policy, and technologies that affect entire industries. He then lays out a structured process for designing a new model and developing it into a profitable and thriving enterprise, while investigating the vexing and sometimes paradoxical managerial challenges that have commonly thwarted so many companies in their unguided forays into the unknown. Business model innovators have reshaped entire sectors--including retail, aviation, and media--and redistributed billions of dollars of value. With road-tested frameworks, analytics, and diagnostics, this book gives executives everything they need to reshape their businesses and achieve transformative growth. Thoroughly updated to, Johnson has also added a new chapter on digital transformation, that presents a framework for digital business models and four new case studies.
Keywords: Kế hoạch chiến lược,Strategic planning; Trường hợp nghiên cứu,Case studies